2018
DOI: 10.1021/acs.inorgchem.8b01288
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and Location of Gd3+ or Tb3+ Ions in Perovskite-Type LaScO3

Abstract: The luminescence properties of Gd or Tb ions at La and Sc sites were investigated in LaScO with a distorted perovskite-type structure (ABO). Although the luminescence of lanthanide ions located at B sites is not common and has not been examined in detail, Gd or Tb luminescence from B sites and A sites is clearly observed in Gd- or Tb-doped LaScO. The differences in the luminescence characteristics concern peak positions, peak shapes, and decay time, which are all influenced by the crystal field and the site sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
8
13
0
Order By: Relevance
“…excitation peaks in the range from 220 to 250 nm. [5][6][7][25][26][27][28][29] The crystal site of Tb 3+ in this assignment is consistent with the results obtained by XRD and XANES measurements. In the PL spectra measured under UV excitation at 247 nm, the Tb 3+ luminescence is composed with two series of transitions from 5 D 3 to 7 F J (J = 6, 5, 4, 3) and from 5 D 4 to 7 F J states.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…excitation peaks in the range from 220 to 250 nm. [5][6][7][25][26][27][28][29] The crystal site of Tb 3+ in this assignment is consistent with the results obtained by XRD and XANES measurements. In the PL spectra measured under UV excitation at 247 nm, the Tb 3+ luminescence is composed with two series of transitions from 5 D 3 to 7 F J (J = 6, 5, 4, 3) and from 5 D 4 to 7 F J states.…”
Section: Resultssupporting
confidence: 90%
“…The XANES spectra in Figure revealed that the crystal field splitting for Tb 5d orbitals in BLTO is as large as 3 eV, which would be larger than the centroid shift. Accordingly, the red-shift of the 4f–5d excitation peak in BLTO:Tb 3+ is primarily attributed to the larger crystal field at the B sites than that at the A sites, which is also observed in some perovskite-type oxides such as LaScO 3 and LaLuO 3 . , The preference of B-site occupation by Tb 3+ in BLTO:Tb 3+ observed in the PLE examination is consistent with the results of the XRD and XANES analyses. It is also worth noticing in the PL spectra that only the Tb 3+ luminescence derived from the 5 D 4 – 7 F J transitions is observed for BLTO:Tb 3+ .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations